Exploring the Representation of Islamic Ideals in the Contemporary Digital Narrative: An Analysis on literacycloud.org - Putra Arianto, Satria Dirgantara; Nuristama, Ramadhina Ulfa; Maretta, Nissa Az-zahra (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This research aims to examine the representation of Islamic teachings and values in contemporary digital narratives. The data of this research is taken from the website literacycloud.org. The selected short stories are part of the "Changemakers" theme, which is included in the website's reading list and features twelve different kinds of short stories. To analyze the intrinsic element in the short stories, the researchers employ qualitative research methods, including structured coding and thematic analysis, to interpret the subjective meaning of the selected data. The study uses the New Criticism theory, emphasizing close reading to uncover the unrevealed Islamic teachings and values expressed and communicated in the text data. This analysis demonstrates the significant presence of Islamic teachings and values in representing and promoting Islam within the digital narratives website. The discovery of an immersive Islamic frame or setting and alignment with Islamic values can convey Islamic ideals such as Tawheed, prophethood, the five pillars of Islam, and more. Thus, this research may foster a deeper understanding of Islamic nuances in literacy interconnected with readers' experiences related to Islamic spirituality in modern society.